Transcutaneous Electrical Nerve Stimulation as a method to relieve pain during childbirth - Agata Wawryków; Katarzyna Korabiusz (Kazimierz Wielki University, 2018)
Transcutaneous Electrical Nerve Stimulation (TENS) is one of the most commonly used non-pharmacological methods of alleviating pain in women during physiological labor after the 37th week of pregnancy. Contraindications to stimulation are: the pacemaker's heartbeat, serious cardiological diseases, epilepsy and mental illness. TENS consists in irritating nerve endings using a flowing current in the vicinity of four electrodes stuck to the patient's body. The place of electrode sticking and parameters are selected individually. The TENS analgesic effect is explained by two mechanisms: the goal control theory and the effect on hormone secretion.